Hygrophila spinosa: A comprehensive review - Kshirsagar, A. D.; Ingale, K. G.; Vyawahare, N. S.; Thorve, V. S. (Pharmacognosy Reviews)
Hygrophila spinosa T Ander, belonging to the family Acanthaceae, is a promising medicinal plant with great economic potential. The medicinal value of H. spinosa has been appreciated in the ancient medical literature. The plant contains terpenoids, alkaloids, flavonoids, and is traditionally known as an aphrodisiac, renal tonic, and for its health-promoting properties. The plant is cultivated throughout India. However, systematic information on the different aspects of this species is not available. In this review, an attempt has been made to present this information.
Keywords: Antioxidant; diuretic; hygrophila spinosa; phytochemistry